EVALUASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RSU PINDAD TUREN MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Oktariyono, Wisnu Rafi; Wijaya, Avid; Rusdi, Achmad Jaelani; Prabowo, Rahmadyo Yudhi; Trisnanto, Puguh Yudho; Marselina, Elystia Vidia (Jurnal Simantec, 2024)
Pindad Turen General Hospital has implemented a hospital management information system (SIMRS) since 2018. However, some users still complain of dissatisfaction with the system. One important factor affecting the successful implementation and use of information technology is user readiness. The level of user readiness in accepting information technology greatly affects the success or failure of the application of the technology. This study used a quantitative descriptive approach with a sample of 36 SIMRS users at RSU Pindad Turen. Data collection techniques were carried out through questionnaires to collect information about SIMRS user perceptions, as well as observations of the system. The variables were measured using dimensions of the Technology Acceptance Model (Perceived Ease of Use, Perceived Usefulness, attitude toward using, behavioral intention, and actual usage). The data obtained was analyzed quantitatively and the results are presented in table form. The study results show the average values for the dimensions of Perceived Ease of Use (3.08), Perceived Usefulness (2.87), attitude toward using (2.67), behavioral intention (3.01), and actual usage (2.89). User perceptions of SIMRS indicate that the system is running well, but still needs improvement due to several shortcomings. Therefore, it is necessary to evaluate the existing information system and further socialize it to officers who use SIMRS. This evaluation aims to measure the benefits of SIMRS implementation and identify potential problems faced by the hospital.Keywords: Evaluation, Technology, Hospital, SIMRS, TAM.